The Development of Canada's Competency Profile for Professional Geoscientists at Entry-to-Practice - Bonham, Oliver; Broster, Bruce; Cane, David; Johnson, Keith; MacLachlan, Kate (Geoscience Canada, 2017)
Competency-based assessment approaches to professional registration reflect the move by professions, both in Canada and around the world, away from traditional credentials-based assessments centred on a combination of academic achievements and supervised practice time. Entry-to-practice competencies describe the abilities required to enable effective and safe entry-level practice in a profession. In 2012, Geoscientists Canada received funding from the Government of Canada's Foreign Credentials Recognition Program. A central component of the funding involved the development of a competency profile to assist in assessment for licensing in the geoscience profession. Work concluded with the approval of the Competency Profile for Professional Geoscientists at Entry to Practice by Geoscientists Canada in November 2014. The Competency Profile comprises concise statements in plain language, setting out the skills and abilities that are required to be able to work as a geoscientist, in an effective and safe manner, independent of direct supervision. It covers competencies common to all geoscientists; competencies for the primary subdisciplines of geoscience (geology, environmental geoscience and geophysics); and a generic set of high level competences that can apply in any specific work context in geoscience. The paper is in two parts. Part 1 puts the concept of competencies in context and describes the approach taken to develop the profile, including: input from Subject Matter Experts (practising geoscientists representing a diverse sampling of the profession); extensive national consultation and refinement; and a validation procedure, including a survey of practising Canadian geoscientists. Part 2 introduces the profile, explains its structure, and provides examples of some of the competencies. The full competency profile can be obtained from the Geoscientists Canada website, www.geoscientistscanada.ca. Future work will identify specific indicators of proficiency related to each competency and suggest appropriate methodologies to assess such competencies. It will also involve mapping the profile to the existing Canadian reference standard, Geoscience Knowledge and Experience Requirements for Professional Registration in Canada.